Assessment of air quality and chemical fingerprints for atmospheric fine aerosols in an Indian smart city. Issue 1 (31st December 2022) - Gupta, Abhishek; Dhir, Amit
ABSTRACT: Ambient air quality of Rajkot city is analyzed along with chemical characterization such as anions, cations, metals and non-sea salts (nss) to understand the chemical footprints on a regional scale. Two sites, rural and urban areaare selected for sampling of PM10, PM2.5, SO2 and NO2, but no major differences are found in ambient air quality.The concentration of ions is found to be high during summer and winter, that is, months of May and December. The concentration of anions and cations in chronological order is Cl − 4 2− 2 − < NO3 − 4 + <Ca 2+ <K + <Na + <Mg 2+ . Similarly, the metal concentration follows the order Na<Mg<Al<Fe<Cr<Zn<Pb<Cu<Mn<As. Majority of metal concentration is lowest during the monsoon season and highest during post-monsoon seasons. Non-sea salts component of fine dust is found highest during the summer season, possibly due to westerly winds from the Arabian sea. Relative contribution by anthropogenic dust was maximum during winter and summer season whereas sea-salt dust in Monsoon and post-monsoon.